PENINGKATAN EKONOMI ANGGOTA KOMUNITAS USAHA KOPERASI CREDIT UNION HATI AMBOINA MELALUI PENDIDIKAN DAN PELATIHAN LITERASI KEUANGAN DAN PEMBUKUAN - Maria Esomar; Hasmia Melati Arifin (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2022)
Maluku province has a financial literacy rate of 36.48%, still below the national index. (OJK, 2019). Cooperatives are expected to have an important role in assisting the government in terms of financial inclusion and literacy. The challenges and problems faced by partners are bad credit problems. Bad loans are caused, among others, due to the lack of understanding and ability of members in managing personal and business finances. The purpose of this activity can help members to have financial plans, plan future expenses, and have savings and also be able to manage their business finances. The procedure for this empowerment activity includes: 1) Coordination with partners regarding the preparation of activity schedules; 2) Preparation of training and material development; 3) Counseling on financial literacy and business bookkeeping; 4) Training on the use of financial instruments and excel applications for business bookkeeping; 5) Assistance and evaluation of the activities carried out. The results obtained are increased understanding of business group community members about financial literacy and bookkeeping, members are able to fill in monthly budget instruments and are able to understand simple bookkeeping and the management of the CU Hati Amboina Cooperative able to use excel bookkeeping applications for further socialization to members of other business groups. Provinsi Maluku memiliki tingkat literasi keuangan 36,48% masih dibawah indeks nasional. (OJK, 2019). Koperasi diharapkan memiliki peran penting dalam membantu pemerintah dari sisi inklusi dan literasi keuangan. Tantangan dan permasalahan yang dihadapi mitra yaitu masalah kredit macet. Kredit macet diakibatkan antara lain karena kurangnya pemahaman dan kemampuan anggota dalam mengelola keuangan pribadi dan usaha. Tujuan kegiatan ini dapat membantu anggota untuk mempunyai rencana keuangan, merencanakan pengeluaran masa depan, dan memiliki tabungan dan juga mampu menata keuangan usaha mereka, Prosedur kegiatan pemberdayaan ini meliputi: 1) Koordinasi dengan mitra terkait penyusunan jadwal kegiatan; 2) Persiapan pelatihan dan pengembangan materi; 3) Penyuluhan tentang literasi keuangan dan pembukuan usaha; 4) Pelatihan penggunaan instrumen keuangan dan aplikasi excel untuk pembukuan usaha; 5) Pendampingan dan evaluasi terhadap kegiatan yang dilaksanakan. Hasil yang diperoleh yaitu meningkatnya pemahaman anggota komunitas kelompok usaha tentang literasi keuangan dan pembukuan, anggota mampu mengisi instrumen anggaran belanja bulanan dan mampu memahami pembukuan sederhana dan manajemen Koperasi CU Hati Amboina mampu menggunakan aplikasi pembukuan excel untuk seterusnya disosialisasikan kepada anggota kelompok usaha yang lain.